RELEVANCE OF PRINCIPALS WITH BK MANAGEMENT IN SCHOOLS - Yenni Elfira; Neviyarni Neviyarni; Riska Ahmad (Widyagogik, 2022)
Management of counseling guidance is one of the most important things in guidance and counseling services that are systematic, clear, organized and rational. Management aspects include planning, organizing, implementing and evaluating. Planning aspects are related to school conditions and situations, namely face-to-face policies for BK activities, and facilities and budgets. The organizing aspect is related to the socialization of how BK works, then to the implementation aspect related to supporting services and activities. Furthermore, the evaluation aspect is related to recording activities, setting performance standards, and the realization of improvements by BK officers. The relevance of the principal affects the implementation, effectiveness, and efficiency of BK management in schools.